P-012 Longer Working Length of the Solitaire Retrieval Device Improves Revascularization. (29th July 2016) - Holloway, W; Akhtar, I; Halpin, J; Martin, C; Akhtar, N
Abstract : Introduction/purpose: Endovascular treatment using stent retrievers are now the standard of care in patients with acute ischemic stroke due to proximal middle cerebral artery occlusion. Recent randomized clinical trials have shown stent retriever recanalization rates (TICI 2 b or higher) surpassing 80%. The Solitaire stent retriever is available in different diameters and lengths. More recently, in August 2014, a 4 × 40 device was made available for thrombus retrieval in the US. While there have been many studies comparing the Solitaire to the other mechanical thrombectomy devices, at present, there have been little to no human data comparing the relatively new 4 × 40 Solitaire device with the older 4 × 20 and 4 × 15 devices. In our presentation we will be looking at the cases in which the 4 × 40 device was deployed and compare the recanalization rates to those achieved with cases treated with the 4 × 20 and 4 × 15 in patients with acute stroke. Materials and methods: Materials used were the Solitaire Revascularization device in the sizes 4 × 40 mm, 4 × 20 mm, and 4 × 15 mm. All devices are identical in diameter but differ in the working length. Methods: This is a retrospective study of 247 stroke patients who underwent clot retrieval using a 4 mm diameter Solitaire device as the first device deployed in a case at Saint Luke's Hospital of Kansas City from 2012 till January 2016. Of the 247 total patients, 34 had undergone initial endovascular treatment with the Solitaire 4 × 40 device. The remainder were either treated with the 4 × 20 or the 4 × 15 Solitaire devices. Successful recanalization was determined as having a final TICI score of 2b or higher (>50% recanalization). Almost every case was performed with a balloon guide catheter inflated in the neck vasculature with aspiration on the guide catheter during Solitaire retrieval. Results: The following Table 1 shows the recanalization rate with the different Solitaire devices. Conclusions: The Solitaire 4 × 40 device showed a statistical trend for achieving better recanalization compared to the shorter devices. However due to our small sample size of patients undergoing treatment with the 4 × 40, further investigation is warranted to determine whether this result is maintained in larger sample size such as the STRATUS registry. Disclosures: W. Holloway: None. I. Akhtar: None. J. Halpin: None. C. Martin: None. N. Akhtar: None.